(3TQM cfR GdObGFbs - (3Rjf GdYGHOjf fLje GdMfaj GdeUQjs; (3MGaX GdOjf CHh GdHQcGJ YHO Gddg Hf CMeO Hf eMehO GdfSaj,J (B710 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CeG HYO aEf CTQa GdYdhe Yde Gdabg hbO bGd ai GdNdGUI Ef GdfXQ ai cJH CUMGHfG ef ZjQ SeGY CaVd ef bjGe Gddjd hbGd Ef JYde Gdabg CaVd ef JYde HGbi GdbQGAGJ s
(3BNQgG (B:s
(3bGdhG hEfeG CNajJ djLJgO ai WdHgG ajfGd HPdc CLQ GdeLJgOjf ai GdYHGOI ceG CNai SHMGfg GdSGYI djchfhG Ydi hLd ef bjGegG HZJI hGddg SHMGfg CYde gPG BNQ GdLRA GdChd ef TQM cfR GdObGFb GdeSei HGdHMQ GdQGFb s
(3GdfSNI HgG MhGTs
(3HChdgG agQS HCHhGH GdcJGHs
(3HgG fXGe GdJYbjHIs
(3HChdgG JQLeI ddTGQM Rjf Hf fLje GdMfai s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3Gdabg GdMfajs